Analisis Konflik Antar Pendukung Dalam Pemilihan Kepala Daerah Di Wilayah Bolaang Mongondow Tahun 2017 - Supriatna, Yana; Liando, Ferry Daud; Pati, Agustinus Bonifacius (JURNAL ILMIAH SOCIETY, 2018)
Conflict is one of the essence of human life and development which has various characteristic. Human beings have different sex, social and economic strata, and law, nation, tribe, religion, belief, political flow, and culture and purpose of life. Along with the rapid technological developments of the above differences of conflict can no longer be avoided and will always occur, the conflict of interest that gave rise to new patterns of social life in the midst of individual communities and groups, this resulted in an disharmony, the event will allow the individual to use responsive or reaction patterns that are unconventional or deviate from the general patterns. The research informant is chosen by purposive sampling. as a source of data or informants who meet the criteria, used as sources of data / informant research, which includes several informants in this study that amounted to 12 people, namely 2 people village government (village head, pantarlih), 2 people from Police Region Bolaaang mongondow (Kabag Ops Polres, Kasi ops Brimob), 2 youth leaders / community, 1 person from elements Commissioner KPU Bolaaang mongondow and 1 person from panwaslu and 4 people from society representing each village in Bolaang Mongondow region. This research data is obtained through in-depth interview with informant, and supported by direct observation and documentation data. The observation is done by going directly to the place where the informant is located, with the intention that the researcher can better understand the answers given by the informant. The data collected in this observation concerns the issue of conflict in the election of regional heads in mongondow ball area in 2017. In-depth interview is intended to obtain information for research interests by way of dialogue between researchers who posed as interviewers with informants or who served as an informer. Documentation data collected relates to conflict analysis among supporters in the election of regional heads in the mongondow ball area in 2017 whether those are government regulations, managerial membership, work program and infrastructure support and other data deemed relevant in supporting data analysis. Thus the data management and data analysis related to the research can know and analyze the conflicts that occur in the election of regional heads in the ballang mangondow.Untuk region of research will be focused in the area of ballang mangondow related to the conflict in the election of regional head.Keywords : Conflict in the Election, Region Head